Место китaйских идиом в китaйской культуре (ҚазҰУ хабаршысы. Шығыстану сериясы, 2018)
In any nonverbal dictionary there are phrases that can be used in one whole, except for single wordsthat express one meaning. It was called an idiom in Chinese grammar. The article examines idioms inChinese, as well as the role, place and meaning of idioms in Chinese culture. In addition, they gave informationabout chyyuyu and its role in the phraseology of the Chinese language and idioms were givenas an example and given a brief history.